Chloroquine-induced pruritus in malaria fever: contribution of malaria parasitaemia and the effects of prednisolone, niacin, and their combination, compared with antihistamine - Adebayo, R. A. (1997)
Aims Chloroquine treatment of malaria fever, results in a generalized pruritus of unknown mechanism in up to 60% of adult Africans, by contrast pruritus is unusual in Caucasians following chloroquine use. Methods We conducted a double-blind, randomized, parallel group study to examine and compare the antipruritic effects of promethazine, niacin, prednisolone and their combination on pruritus induced by chloroquine, in 28 historical itching patients with parasitologically proven malaria fever. We also evaluated the role of the antecedent malaria parasite density in the severity of chloroquine pruritus intensity. Results The concurrent administration of chloroquine (2.1g base total dose) with prednisolone caused a statistically significant reduction in the pruritus AUC (0, 72 h) (P<0.001 ANOVA) compared with the antihistamine promethazine alone. The areas under the pruritus intensity-time curve were promethazine 105±28 (units h), niacin 76±22, prednisolone 28±24, and prednisolone and niacin 34±17 (P<0.001 ANOVA). The 95% confidence interval for the difference in the pruritus AUC between prednisolone and promethazine was 8.4 to 145.6 units h. There was a statistically significant and positive correlation between the pruritus intensity (AUC 0, 72 h) and the malaria parasite load in the itching subjects, not receiving prednisolone (n=9) (r=0.73, P=0.026 ANOVA). Conclusion A single oral dose of prednisolone (10 mg) may be preferable to the antihistamine promethazine (25 mg) as an antipruritic agent for concurrent prescription with chloroquine in individuals predisposed to severe itching. Malaria parasite clearance and clinical amelioration were unaffected by any of the treatments.